The Administrative Impact of Empowerment and Flexibility in Achieving Organizational Commitment: Dampak Administratif Pemberdayaan dan Fleksibilitas dalam Mencapai Komitmen Organisasi - Qutaiba Theyab Ahmed (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Organizational commitment is a key factor that influences employee performance and institutional stability in modern organizations. Specific Background: Many institutions increasingly adopt administrative empowerment and job flexibility as managerial practices intended to strengthen employee participation, autonomy, and organizational attachment. Knowledge Gap: Despite growing attention to empowerment practices, limited empirical studies have examined their combined role with job flexibility in shaping organizational commitment within academic institutions. Aims: This study investigates the administrative impact of empowerment and job flexibility in achieving organizational commitment at the University of Samarra. Results: Using a descriptive-analytical method and questionnaire data collected from 40 administrative employees, statistical analysis indicates that empowerment dimensions, including delegation of authority, training, participation, and information sharing, together with job flexibility, are significantly associated with higher levels of organizational commitment. The findings also reveal that limitations in the work environment and reduced participation in decision-making may weaken these managerial practices. Novelty: The study provides an integrated examination of empowerment and flexibility as managerial mechanisms influencing organizational commitment within a university context. Implications: The findings highlight the importance of creating supportive organizational environments, improving communication systems, and expanding employee participation to strengthen commitment and institutional performance. Keywords: Administrative Empowerment, Job Flexibility, Organizational Commitment, Organizational Behavior, University Management Key Findings Highlights Empowerment dimensions relate to stronger employee attachment within institutions Flexible work practices support participation and managerial autonomy Organizational environment conditions shape commitment outcomes